PROCEDURE FOR ASSESSING THE SECURITY OF AN INTEGRATED PLATFORM FOR THE DEVELOPMENT OF CORPORATE APPLICATIONS - V. A. Lomazov; V. I. Lomazova; V. V. Lomakin; R. G. Asadullaev (Современная наука и инновации, 2022)
The problem of ensuring the protection of information in administrative information systems is considered.